Processo de integração ensino-serviço: a educação permanente em saúde como estratégia para o fortalecimento da gestão do SUS - Ferraz, Edinalva de Moura (2023)
Management in/of the Unified Health System is a complex activity, which requires understanding from the management teams and a set of skills and competences to overcome the challenges experienced in this area. And the integration between health services and universities can be an important strategy to mitigate this complexity. The literature shows that these articulations are important for the quality of care, but it is still incipient to carry out studies that investigate the teaching-service integration from the perspective of the management of this system, in particular, when this integration is anchored in the assumptions of Permanent Education in Health. Thus, the present study aimed to analyze the repercussions of a teaching-service integration process through Permanent Health Education, to strengthen the management of the Unified Health System. It was carried out in two health regions, located in the northern macro-region of the State of Paraná. This a qualitative workshops that structured this process, comprehensive stude that used two complementary techniques to obtain and analyze the empirical data. At first, participant observation was carried out during the workshops that took place in the 16th Health Region, which had an average of 33 people and that structured this process of Permanent Education in Health, named PROGESTÃO, wich took place between April and December 2019. In the second moment, interviews were carried out, from July to December 2020, with people who stood out in terms of participation, carrying out the dispersion tasks and exchanging knowledge with the other members of the group during the workshops. Due to the pandemic caused by the Coronavirus, these interviews were carried out remotely, by the author of the thesis, with the support of a semi-structured script, which contained triggering questions for the dialogue, which addressed the process developed, as well as its repercussions for the practice of health management. The methodological theoretical framework used for extracting and analyzing data from participant observation and interviews was critical hermeneutics, proposed by Paul Ricouer, which considered, among other aspects, the temporality of discourse, as well as its subjectivity and representativeness. The result of this thesis was presented in the Scandinavian model, divided into two scientific articles. The first article deals with the process of Permanent Education in Health developed. Written on the experience report format, it is structured in five sections: the first describes the context in which the experience was developed, elucidating reasons, actors and the location in which it took place; the second presents the work proposal, the preparation of the workshops and the methodological resources used; the third reports the path taken in its operationalization; the fourth discusses the interdisciplinarity characteristics existing in the process and the last presents some considerations. The proposal proves to be a powerful strategy to promote dialogue, qualify and make reflective work in the field of health management among different actors and institutions, especially in the context of the state's health and fiscal crisis. The second manuscript, developed under the aspect of a qualitative study, analyzed the repercussions of this process of Permanent Education in Health. The results revealed challenges and potentialities of the Continuing Education process in the scope of health management, as well as repercussions for the performance of the management team in its locus of action. Despite the challenges revealed, such as the incipient qualification of the team and the difficulty of institutionalizing the National Policy on Permanent Education, professionals recognized the importance of teaching-service integration in promoting training processes that use active methodologies and provide collective spaces for dialogue The EPS process experienced during the course had repercussions on greater integration between people who participate in municipal management processes, a feeling of belonging and commitment to management, incorporation of EPS processes into daily management, with emphasis on coping with problems arising from the pandemic and in the process of defining the use of resources by the management team. It is essential to promote qualification processes that consider the subjects' needs, the context of action and the singularities of the professionals who work in the management of the SUS. This thesis also demonstrated that the complexity of management experienced in the context of the SUS can be alleviated through partnerships between the world of education and the world of work.